Risk factors and prediction model for mental health in Chinese soldiers - Zhao, Mengxue; He, Ying; Tang, Quan; Wang, Ni; Zheng, Haoxin; Feng, Zhengzhi (Frontiers in Psychiatry, 2023)
Introduction This study aimed to explore potential risk factors for mental health concerns, and the prediction model for mental health concerns in Chinese soldiers was constructed through combined eligible risk factors. Methods This cross-sectional study was performed on soldiers under direct command from Gansu, Sichuan, and Chongqing in China, and the soldiers were selected by cluster convenient sampling from 16 October 2018 to 10 December 2018. The Symptom Checklist-90 (SCL-90) and three questionnaires (Military Mental Health Status Questionnaire, Military Mental Health Ability Questionnaire, and Mental Quality Questionnaire for Army Men) were administered, including demographics, military careers, and 18 factors. Results Of 1,430 Chinese soldiers, 162 soldiers presented mental disorders, with a prevalence of 11.33%. A total of five risk factors were identified, including serving place (Sichuan vs. Gansu: OR, 1.846, 95% CI: 1.028–3.315, P = 0.038; Chongqing vs. Gansu: OR, 3.129, 95% CI, 1.669–5.869, P = 0.003), psychosis (OR, 1.491, 95% CI, 1.152–1.928, P = 0.002), depression (OR, 1.482, 95% CI, 1.349–1.629, P < 0.001), sleep problems (OR, 1.235, 95% CI, 1.162–1.311, P < 0.001), and frustration (OR, 1.050, 95% CI, 1.015–1.087, P = 0.005). The area under the ROC curve by combining these factors was 0.930 (95% CI: 0.907–0.952) for predicting mental disorders in Chinese soldiers. Conclusion The findings of this study demonstrate that mental disorders and onset in Chinese soldiers can be predicted on the basis of these three questionnaires, and the predictive value of the combined model was high.